Review of current trends in agent-based modeling of building occupants for energy and indoor-environmental performance analysis. (15th April 2020) - Berger, Christiane; Mahdavi, Ardeshir
Abstract: This paper is concerned with the representation of building users in simulation applications that explore buildings' energy and indoor environmental performance. In recent years, efforts have been made to develop more detailed occupancy-related input data for building performance simulation. For instance, instead of using standard occupancy schedules or simple rule-based behavioral models, stochastic formalisms have been proposed to more realistically capture occupants' patterns of presence and behavior in buildings. Specifically, agent-based modelling has been suggested to provide an adequate tool to capture the complexity and dynamics of building occupants, both as individuals and as groups. In this context, the present paper entails a brief discussion of agent-based modeling followed by a concise review of a number of recent publications reporting on the application of agent-based modeling in the built environment domain (especially regarding buildings' energy and indoor-environmental performance). The paper concludes with remarks on the future prospects of agent-based modelling in building-related applications. Highlights: The contribution addresses current trends in agent-based modeling (ABM) of building occupants. The review focuses on ABM application in the context of buildings' energy and indoor environmental performance. Agent-based modelling has the potential to capture the complexity and dynamics of building occupants. Existing work is insufficiently grounded in an empirically-based understanding of occupants' behavior in buildings.